Antecedents of Communal Engagement, Group Self-esteem, and Trust in member on Loyalty in Social Network Site - Suebboon, Oranuch; Rangsikanpum, Thanaphorn; Arun, Suthasinee; Narintrangkul Na Ayudhaya, Chompoonut; Srikanlayaniwart , Sasinipa; Narakorn, Prasittichai (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The objectives of this research is to examine factors influence Customer Loyalty as follows: Group Self-Esteem, Communal Engagement and Trust in Members who buy products from social network site. The researchers used quantitative method to 519 customers who buy products from social network site and analyzed by Structural Equation Model analysis from AMOS. The research findings: Communal Engagement, Trust in Member, and Group Self-Esteem have significantly positive influence on Customer Loyalty (p < .05).